2014
DOI: 10.1016/j.toxrep.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead acetate on testicular function and caspase-3 expression with respect to the protective effect of cinnamon in albino rats

Abstract: HighlightsLead acetate reduced the sperm cell concentration, increased sperm abnormalities and decreased the superoxide dismutase (SOD) and catalase activities in male rats.Addition of cinnamon to lead acetate enhanced the viability of the spermatozoa, preserved the sperm cell concentration and improved the level of SOD and catalase activities.The expression of androgen receptor was reduced in testis of lead treated rats associated with increased the level of caspase-3 expression.Cinnamon exhibited protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
78
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 22 publications
17
78
0
1
Order By: Relevance
“…The present study demonstrated the proved results of lead intoxication in lead acetate treated group. The testicular dysfunction was reflected in the semen analysis with remarkable asthenospermia, oligospermia and high percent of abnormalities, which is similar to previous study (Elgawish and Abdelrazek, 2014). Earlier, it has been proved that accumulation of lead in the testis has antispermatogenic effect (Fahim et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The present study demonstrated the proved results of lead intoxication in lead acetate treated group. The testicular dysfunction was reflected in the semen analysis with remarkable asthenospermia, oligospermia and high percent of abnormalities, which is similar to previous study (Elgawish and Abdelrazek, 2014). Earlier, it has been proved that accumulation of lead in the testis has antispermatogenic effect (Fahim et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Lead induced oxidative stress promotes hydrogen peroxide (H 2 O 2 ) generation [4]. Lead acetate (LA) has been shown to decrease male reproductive organ function by causing testicular tissue alterations in the histological patterns of the testis [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Sub-chronic low Pb exposure produces nephrotoxicity in vivo and in vitro [36], as well as infertility [56] in rodents. To protect against free radical damage, cells activate anti-oxidant enzymes such as SOD1 (Cu/Zn superoxide dismutase).…”
mentioning
confidence: 99%